Osmotic component of water potential and stress adaption of adult Pedunculate oaks (Quercus robur L.) in stands with different tree density - Čater, Matjaž (Zbornik gozdarstva in lesarstva, 2010)
Pressure volume curves were applied to define differences in stress adaptation between two managed forest complexes and virgin forest remnant; in Murska šuma, Krakovo forest and Krakovo old growth forest. Species response between adult stands after stronger thinning and comparable stand without any silvicultural measures within same forest complex was compared in two consecutive years, 2003 and 2004. Significant differences in osmotic potential (full turgor) component for plots in Murska šuma in 2003 as well as in Krakovo forest between managed forest and old growth-forest were confirmed. In all cases, values became more negative, indicating slight capability of oaks to adapt with increasing drought stress. Reaction/stress adaptation of forests after thinning indicated well adapted mechanism to address drought stress in spite of the age. We may connect such improved drought response with increased individual space for growth and lower stand density.
Keywords: dob; nižinski gozdovi; osmoza; prilagoditve; Quercus robur L.; sušni stres; vodni potencial